2016
DOI: 10.1016/j.jcou.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of support of Co-Na-Mo catalysts on the direct conversion of CO2 to hydrocarbons

Abstract: This study of the effect of support of Co-Na-Mo based catalysts on the direct hydrogenation of CO2 into hydrocarbons (HC) provides guidelines for the design of catalysts for CO2 conversion.We demonstrate that the surface area of the support and the metal-support interaction have a key role determining the cobalt crystallite size and consequently the activity of the system. Cobalt particles with sizes < 2 nm supported on MgO present low reverse water gas shift conversion with negligible Fischer-Tropsch activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 42 publications
1
52
0
Order By: Relevance
“…Here, it is important to note that there is no significant effect of pressure on the conversion of CO 2 below 270°C. This fact indicates that CO 2 ‐FT reaction will yield desirable results with bit lower chain HCs at low pressure and low temperature, which is supported by various experimental studies conducted at atmospheric pressure . However, increase in temperature up to 477°C is favorable for long chain HCs synthesis at higher pressure .…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Here, it is important to note that there is no significant effect of pressure on the conversion of CO 2 below 270°C. This fact indicates that CO 2 ‐FT reaction will yield desirable results with bit lower chain HCs at low pressure and low temperature, which is supported by various experimental studies conducted at atmospheric pressure . However, increase in temperature up to 477°C is favorable for long chain HCs synthesis at higher pressure .…”
Section: Resultsmentioning
confidence: 69%
“…Owen et al . have reported the formation of HCs from CO 2 on Cobalt catalsyts at atmospheric pressure with a significant conversion. In the view of above studies, CO 2 hydrogenation provides new opportunities for the development of catalytic processes and sustainable energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] However,they are poor RWGS catalysts,a nd thus unsuitable for CO 2 hydrogenation.T he C 2 -C 4 hydrocarbon productioni sl imited,w ith methane as main product. [66] Despite this, cobalt was used as dopanti nF e/K catalysts. Adding a small amount of Co (2.6 wt %) to aF e( 12.4 wt %) catalyst showedh igher CO 2 conversion than an unpromotedF ec atalyst.…”
Section: Cobalt-based Catalystsmentioning
confidence: 99%
“…Precious metals (Pd, Pt, Ru, Rh) on SiO 2 have been used in the reverse water gas shift reaction, while catalysts for the Fischer-Tropsch process are usually Fe or Cobased, with recent innovations towards one-pot reactions (see e.g. Mattia et al, 2015;Owen et al, 2016;Prieto, 2017) following early work (Dorner et al, 2010) that showed conversion of CO 2 to hydrocarbons (41% conversion and a C2-C5+ selectivity of 62%) using a doped Fe-based system. The potential for using biogenic catalysts has not been explored although a paradigm hybrid bio-magnetite/Pd(0) catalyst has been reported .…”
mentioning
confidence: 99%